Effect of a noncircular shape of the torus on the magnetic surfaces of l=1 torsatron - Kotenko, V. G. (Вопросы атомной науки и техники, 2015)
The paper presents the numerical calculation results on the magnetic field produced by one helical winding laying on the surface of a noncircular torus. The influence of the chosen poloidal cross-section shape of the torus on the parameters of the closed magnetic surface configuration has been investigated. The calculation results show that the change of a torus with circular cross-section by a torus with noncircular cross-section in the l=1 torsatron under consideration decreases the value of the mirror ratio on the magnetic surfaces by a factor of ~8. And other parameters of magnetic surfaces were changed no more than by a factor of 1.5 to 2. A feasibility of the simplest torsatron with central stochastic magnetic field line region is discussed.